PENGARUH PENAMBAHAN LEMAK KAKAO TERHADAP SIFAT FISIK DAN SENSORIS MEISES - , ARDIAN WAHYU WIDIYANTORO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Meises is trimmed chocolate granule used as decoration and flavor enrichment in cake, doughnut and ice cream. Meises has various variation like brown meises, milk-flavour meises, and various colour meises. This study aims to determine the effect of addition of cocoa butter concentration on the physical properties of meises which are hardness, colour, and melting point, and to acknowledge and determine the amount of cocoa butter used to produce panelistpreferred meises. Addition of cocoa butter concentration of 15%, 30% and 45% is done. Parameters measured were hardness, colour, melting point and sensory properties. Hardness is determined using the Universal Testing Machine, colour using the Chromameter, melting point using the capillary tubes method and sensory properties using the hedonic sensory method. The results showed that an average addition of 15% cocoa butter concentration will decrease the hardness level chocolate meises around 27 to 58%. Increased concentration of cocoa butter has a tendency to lower the hardness level of chocolate meises. Increased concentration of 15%, 30% and 45% cocoa butter in meises will increase the brightness of the color, but will lower the appearance of red and yellow color. Meises with the addition of 15% - 30% cocoa butter concentration have a high melting point which is optimal in manufacturing chocolate meises. Preferred chocolate meises product is chocolate meises with 30% cocoa butter concentration which has a hardness level of quite hard and dark brown appearance.